The Schooling of Young Indigenous Girls in the School District of Ngo - Okoua Beatrice Perpetue (RIRAI Publisher, 2022)
Education is the basis of all societies. Its aim is to transform undifferentiated beings at birth into beings who are members of societies capable of contributing to their substance and their development. It constitutes a catalyst for the reception of knowledge and seems to be the best shared thing in the world. School has become the preferred environment for Bantu and indigenous children. But indigenous children in particular, girls always drop out of schools temporarily and permanently. This study was carried out in the school district of Ngo in the department of Bateke plateau located 250 km from Brazzaville. Data collection was facilitated by the questionnaire, semi-structured interview, observation and documentary analysis. The results obtained confirm the main hypothesis, according to which there are socio-cultural and economic factors that hinder the schooling of young indigenous girls the main causes: unfavorable living conditions parental illiteracy, solicitation of labor work of indigenous girls, the language of teaching and learning.